Karakteristik Klinis Corona Virus Disease (COVID-19) pada Kasus Anak-Anak di Dunia - Rachman Aziz; Risti Graharti (Medula, 2020)
Corona virus disease-19 (COVID-19) is a global health crisis problem. The clinical characteristics of disease progression and outcome in children and young adults appear to be much milder than in older people. The incidence of COVID-19 in children aged 10-19 years was 549 / 72,314 or 1% of all cases, while the age group <10 years was 416 / 72,314 (0.9%) cases. Compared to adults, the number of confirmed children cases is very low and the severity and mortality is even lower. Indonesia has 450 cases of COVID-19; 38 of them died as of March 21, 2020. The incubation period for COVID-19 in children based on case reports around the world ranges from 2 to 10 days. Data suggest 13-15% of virologically positive children may be asymptomatic. The most common symptoms described in the early phase of COVID-19 in children were fever (50%) and mild cough (38%). Other clinical features that can appear are sore throat, rhinorrhea, sneezing, myalgia, fatigue, diarrhea, dizziness, skin rash and vomiting.